Corporate environmental criminal liability in Spain and the participation of the environmental non-governmental organizations (ENGOS) (2020)
This paper has the aim of pointing out the environmental enterprises’ criminal liability in Spain. Considering this, it proposes an environmental criminal policy based in two main ideas: the participation of the Environmental NonGovernmental Organizations in the elaboration of criminal compliance programmes in a framework where the self-enforcement is common and the access to environmental justice of this organizations Keywords: Spanish Enterprises Criminal Liability. ENGO. Compliance Programmes. Environmental Justice. Participation Rights.